Asymmetric Omphalopagus in a Triplet after In Vitro Fertilization: A Rare Case of Conjoined Twinning - Samir Jabari; Roman Carbon; Manuel Besendörfer; Arndt Hartmann; Oliver Rompel; André Hoerning; Stephan Söder (Case Reports in Pediatrics)
Introduction. Asymmetric omphalopagus is a rare situation of conjoined twinning, in which a grossly defective twin is attached to the thorax and upper abdomen of the main twin. We describe a case of an asymmetric omphalopagus accompanied by a normal triplet after assisted reproductive technology (ART) and tried to further characterize the all aspects of the conjoined twins. Case Presentation: Perioperative diagnostic imaging was carried out followed by an autopsy to evaluate all aspects of the parasite accompanied by histological, immunohistochemical, and molecular biological evaluation. The parasite had well-developed lower extremities as well as upper extremities with a cleft hand syndrome. The sex was nondeterminable, but DNA fingerprinting revealed that both parasite and autosite are monozygotic, so are females. There was no sign of any axial skeleton or central nervous system. We found a rudimentary rectum with a nonpervious anus, a kidney, ureter, urinary bladder, and a blind-ending urethra. The blood supply of the parasite was connected to the vessel system of the autosite. Conclusions. To our knowledge, only two cases of parasitic omphalopagus after ART have been described to date. Altogether, 52 cases have been reported, and in most of them, the parasites were successfully separated.